The Oestrogenis and Cytotoxic Effects of the Extracts of Labisia pumila var. alata and Labisia pumila var. pumila In Vitro - Jamia A.Jamal,; Houghton P.J,; Milligan S.R,; Ibrahim Jantan, (2003)
Aqueous, acid hydrolysed and ethanolic extracts of the roots and leaves of Labisia pumila var. alata and Labisia pumila var. alata and Labisia pumila var. pumila were investigated for their oestrogenic and cytotoxic effects using Ishikawa cell line by performing an in vitro Ishikawa alkaline phosphatase assay and an in vitro protein assay, respectively. Among them, only the ethanol extract of the root of L. pumila var. alata exhibited a weak oestrogenic activity at 10-50 mg/ml. The samples that exhibited significant cytotoxic effect were the ethanol extract of the roots of L. pumila var. alata (IC50 433 mg/ml), and the aqueous extracts of the roots of L. pumila var. alata (IC50 433 mg/ml) and the leaves of L. pumila var. pumila (IC50 458 mg/ml).